Serum magnesium is associated with long-term survival of non-ST-elevation myocardial infarction patients. (3rd October 2022) - Shechter, M; Cohen, H; Sharon, A; Koren-Morag, N; Grossman, E; Maor, E
Abstract: Background: In Israel, the rate of drinking water from desalinated sea water has increased dramatically to 60% in the last two decades. However, desalinated water lacks magnesium. Hypomagnesemia is associated with adverse cardiovascular outcome. Aim: To investigate the association of admission serum magnesium levels (sMg) with long-term survival of non-ST-elevation myocardial infarction (NSTEMI) patients in the light of increased use of desalinated sea water. Methods: A single-center, retrospective cohort of consecutive petients who were hospitalized with NSTEMI as their primary clinical diagnosis between August 1, 2008 to March 31, 2021. Multivariate Cox regression model was applied for mortality risk. Results: Study population included 5, 675 NSTEMI patients with a mean age of 71±13 years (range 25 to 110), of whom 3, 820 (67%) were males. Mean and median sMg levels were 2.0±0.2 (0.5–6.8), 2.0 mg/dL, respectively. During mean follow-up of 4.1±2.9 years (0–14), 2, 238 (39%) patients died. Mortality rate was u-shaped when associated with sMg levels (Figure 1) and the study cohort was divided into quintiles according to the sMg levels (≤1.80; 1.81–1.94; 1.95–2.00; 2.01–2.20; ≥2.21). Patients in the highest compared to the lowest sMg quintiles had significantly higher incidence of renal dysfunction with lower eGRF EPI (62±32 vs 76±26 ml/min/1.73 m 2, p<0.001) and lower fasting serum glucose (102±37 vs 115±46 mg/dL, p<0.001). All-cause mortality rate was the highest in the lowest and highest sMg quintiles (48%, 33%, 32%, 33% 54%, respectively, p<0.00). Compared to the 2nd sMg quintile (1.81–1.94 mg/dL), with the lowest mortality risk, the lower sMg quintile was associated with a significant and indpendent 24% increased risk of death in a multivariate model (95% CI 1.07–1.44, p<0.001), while the highest quintile was associated with 48% increased risk (95% CI 1.25–1.74, p<0.01) (Figure 2). Conclusion: Admission low sMg is associated with long-term all-cause mortality in NSTEMI patients. Additionally, long-term mortality is also high in NSTEMI patients with renal dysfunction-induced high sMg levels. Funding Acknowledgement: Type of funding sources: None.